Modelling of water-to-gas hollow fiber membrane humidifier - Pandey, R.; Lele, A. (Chemical Engineering Science, 2018)
A microscopic mathematical model is developed for membrane based water-to-gas humidification by rigorously accounting for phase equilibrium between the membrane and water phases as well as membrane and gas phases in addition to the coupled heat and mass transfer occurring across the membrane. The model is then integrated along the length of a hollow fiber membrane humidifier in order to predict humidifier performance as a function of design variables, operating variables and operational strategies. For realistic values of membrane thickness and flow parameters, the model suggests that while membrane-gas interfacial resistance alone is crucial for heat transfer, the vapor transfer is governed by the combined resistances of diffusion within the membrane and membrane-gas interface. The model is validated against experimental data obtained using a commercial hollow fiber
Keywords: Coupled Heat and Mass; Fuel Cell Applications; Humidification; Phase equilibrium; Proton exchange membrane; Water-to-gas

Effect of processing conditions on the rheological properties of blends of ultra high molecular weight polyethylene with high‐density polyethylene - Chaudhuri, K.; Poddar, S.; Pol, H.; Lele, A.; Mathur, A.; Srinivasa Rao, G.S.; Jasra, R. (Polymer Engineering and Science, 2019)
Blends of high‐density polyethylene (HDPE) with small amounts of ultra‐high molecular weight polyethylene (UHMWPE) were prepared by melt mixing in a twin‐screw microcompounder. Two types of UHMWPE differing in their states of chain entanglement were used. The blend composition, time of mixing, and rotation speed of the screws were varied. Rheological properties of the blends were studied in oscillatory shear and uniaxial elongational tests. Reduction in phase angle measured in dynamic shear rheology and increase in extensional strain hardening were found to be useful indicators for quantifying the extent of mixing of the two components. Although the disentangled UHMWPE showed reasonable mixing with HDPE during typical residence times of melt compounding operations, the entangled UHMWPE remained essentially undissolved. The extent of mixing increased with mixing time and screw speed. POLYM. ENG. SCI., 2018. © 2018 Society of Plastics Engineers

Study of rheology and plug assist thermoforming of linear and branched pp homopolymer and impact copolymer - Marathe, D.; Shelar, S.; Mahajan, S.; Ahmad, Z.; Gupta, S.; Kulkarni, S.; Juvekar, V; Lele, A. (International Polymer Processing, 2019)
Polypropylene (PP) is one of the fastest growing thermoplastic polymers in the world, second only to polyethylene. This is primarily due to its excellent balance of physical and chemical properties at a lower cost. PP however possesses low melt strength on account of its linear structure and hence is not easily amenable to processing techniques that involve free surface stretching deformations like thermoforming, blow molding and extrusion film casting. One way to enhance the melt strength of PP is to incorporate long chain branches in its molecular architecture. The present study focuses on the impact of rheology of linear and branched PP on their thermoforming characteristics. Two grades each of linear and long chain branched (LCB) PP homopolymer and impact copolymer (ICP) were used. It was observed that the LCB-PP homopolymer and LCB-ICP showed higher flow activation energy, reduced value of loss tangent and nearly equal frequency dependence of storage and loss moduli in shear rheology. Also, a strong strain hardening behavior was displayed in extensional rheology by the LCB grades. Plug assist thermoforming experiments were carried out to assess the effect of long chain branching on surface strain and thickness distribution for axisymmetric cups of two draw ratios. Biaxial surface strain maps of the formed cups were quantified using Grid Strain Analysis (GSA). Thermoformed cups made from LCB-PP homopolymer and LCB-impact copolymer showed lower surface strain and overall higher thickness as compared to cups made from their linear counterparts, which is in accordance with what might be expected from their rheology.